INTER-SECTOR COLLABORATION IN SUPPORTING THE WELFARE OF UMKM: A LITERATURE REVIEW - Gunawan Widjaja (CV. Adiba Aisha Amira, 2024)
Inter-sector collaboration has been recognised as a key component in improving the welfare of Micro, Small and Medium Enterprises (MSMEs). The purpose of this literature review is to explore how collaboration between the government, private sector, educational institutions, and communities can contribute to the growth and prosperity of MSMEs. Through a comprehensive analysis, this study identifies that effective collaboration enables MSMEs to overcome various challenges such as limited access to capital, technology, and efficient business management. In addition, the study shows that cross-sectoral cooperation promotes innovation, adaptability and sustainability for MSMEs. Such collaboration also plays a role in strengthening local economic development by creating jobs and promoting equitable income distribution. Based on this literature review, it is concluded that synergy between various sectors is an important catalyst in realising sustainable growth of MSMEs that can contribute significantly to the national economy. This conclusion confirms the importance of an inclusive and integrated collaboration strategy to develop a supportive ecosystem for MSMEs, which in turn will support general welfare and overall economic progress.